The impact of exercise on mitochondrial biogenesis in skeletal muscle: A systematic review and meta-analysis of randomized trials - Abrego-Guandique Diana Marisol; Aguilera Rojas Nalia Mercedes; Chiari Aldo; Luciani Filippo; Cione Erika; Cannataro Roberto (Biomolecular Concepts)
The interaction between exercise and mitochondrial biogenesis in skeletal muscle is fundamental to human physiology, with important implications for health and athletic performance. While exercise is known to stimulate mitochondrial biogenesis, the effectiveness of varying-intensity exercise remains unclear. This systematic review and meta-analysis aimed to evaluate the impact of physical activity on mitochondrial biogenesis pathways in skeletal muscle and identify key biomolecular markers in healthy individuals. Among these, PGC-1α emerged as the most consistently reported marker. The meta-analysis showed a significant increase in PGC-1α expression following endurance exercise, with a pooled effect size of Hedge’s g = 1.17 (95% confidence interval: 0.14–2.19, I 2 = 84.5%), indicating a large effect with substantial heterogeneity. Subgroup analyses revealed that both interval and continuous endurance training produced large effects (Hedge’s g = 1.29 and 1.01, respectively), with no significant difference between modalities (p > 0.05). These findings confirm that exercise induces significant molecular and structural mitochondrial adaptations, with responses influenced by exercise type, intensity, and duration. This underscores exercise as a potent stimulus for mitochondrial biogenesis, supporting its role in promoting metabolic health and physical performance.